Superhydrophobic MOFs modified by rosin acid with excellent stability for oil-water separation and catalysis - Siya Guo; Siwei Dai; Junkai Fang; Qingfang Xiong; Yucheng Zhou; Wenting Wang; Min Zhang; Chuntao Kuang; Guoen Yang; Zhaoshuang Li (Journal of Water Process Engineering, 2026)

137Cs and 210Pbex dating to assess sedimentation rates in terraced valley floor fields - Yunqi Zhang; Shucui Liu; Dan Li; Wei Li; Qingfang Tan; Yi Long; Guirong Hou; Ziteng Luo; Haiyan Yi; Yong Wang; Bo Tan (Journal of Hydrology, 2026)

Computationally tailoring the adsorption behavior of ZrSe2 for SF6 decomposition species in GIS: Mechanistic insights into Cu2O/Ag2O functionalization - Liwen Zhou; Feng Yang; Yingang Gui; Jiagui Tao; Jie Li; Jitao Zhang; Qingfang Zhang; Gang Wei; Zhengqin Cao; Qianglong Yang (Environmental Research, 2026)

A novel method of determining optimal GNSS station density for NWP - Qingzhi Zhao; Qingfang Chen; Yongjie Ma; Haojie Li; Anbang Wu; Ming Liu; Yibin Yao; Hong Liang; Hongwu Guo; Yuxing Zhao; Jing Yang; Qingyuan Guo; et al. (Advances in Space Research, 2026)

Evaluation of fermentation performance of yeast strains isolated from Passiflora ligularis - Shuqing Feng; Qin Zhu; Jian Cai; Qingfang Xu; Jie Li; Qian Sun; Ying Mao; Ling Zhu (Archives of Microbiology, 2026)

Adsorption and sensing performance of Aun(n = 1–3) cluster-modified WSe2 for harmful gas molecules in barn environments: A DFT study - Yingang Gui; Qirui Hu; Guojiang Zhang; Jie Li; Jiagui Tao; Jitao Zhang; Qingfang Zhang (Journal of Environmental Chemical Engineering, 2026)

Intrinsic, Cu-, Ag-, and Au-modified Janus NbSSe for detection of SF6 decomposition harmful gases: DFT calculations and gas-sensing mechanism verification - Qianglong Yang; Yingang Gui; Jie Li; Jiagui Tao; Jitao Zhang; Qingfang Zhang (Journal of Environmental Chemical Engineering, 2026)

Waterlogging-induced wheat yield loss is reduced by ditch-buried straw return via increasing soil water infiltration and enhancing plant tolerance - Qingfang Luo; Yuekai Wang; Xinhu Guo; Yue Zhang; Zhenzhen Li; Yanling Li; Fengmin Li; Haishui Yang (Plant and Soil, 2026)

1H NMR guided isolation of flavans from Broussonetia papyrifera and their α-glucosidase inhibitory activity - Tingting Guo; Kepu Huang; Qingfang Wang; Chen Peng; Xingping Zhang; Congxi Gao; Kou Wang; Hongping He; Mingming Li (Phytochemistry, 2026)

Optimizing fertilizer and planting density to stabilize yields and improve water use efficiency in rain-fed wheat–maize rotations - Xueni Yang; Shujie Sun; Haocong Li; Ziyan Guo; Chi Ma; Bo Liu; Wei Zhang; Ruixia Ding; Peng Zhang; Tiening Liu; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2026)

Monoatomic copper anchored on tubular carbon nitride with high carbon/oxygen abundance via 2-methylimidazole direction: synthesis and catalytic performance - Jianghe Chen; Qingfang Zhang; Xia Zhao; Tianfeng Wang; Yabin Li; Zuoyan Chen; Wenjing Xu; Linhai Yang (Environmental Geochemistry and Health, 2026)

Five undescribed 1,3-diphenylpropanes from the leaves of Broussonetia papyrifera - Tingting Guo; Qingfang Wang; Chen Peng; Xingli Zhang; Kepu Huang; Kou Wang; Hongping He; Mingming Li (Phytochemistry Letters, 2025)

Coplanar DCA-based hypofractionated stereotactic radiotherapy for very small brain metastasis from non-small cell lung cancer: treatment planning comparison with coplanar VMAT and preliminary clinical outcome - Shipai Zhu; An Li; Jia Liu; Qin Deng; Qingfang Li; Jialu Lai; Lin Zhou (Physical and Engineering Sciences in Medicine, 2025)

Dammarane triterpenoids with anti-inflammatory and promoting glucose uptake activities from the leaves of Cyclocarya paliurus - Xiaoqin Liang; Qingfang Zheng; Biqun Zou; Yanqin Li; Liwei Pan; Chenyang Ren; Jiwen Xin; Bo Yang; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanling Cui; et al. (Phytochemistry, 2025)

Structure-activity relationships and mechanisms of natural polysaccharides in modulating neurological disorders via the microbiota-gut-brain axis - Yulin Song; Qingfang Deng; Jiawen Li; Ruhai Chen; Dan Li; Shenglin Wang; Baitong Jing; Xin Zhou (Carbohydrate Polymers, 2025)

Ultrasound-assisted phosphorylation on the functional and structural properties of fish gelatin - Qingfang Ying; Bin Hu; Yijia Li; Liangying Xu; Wenge Yang; Shengnan Zhan; Changrong Ou; Tao Huang (Food Hydrocolloids, 2025)

Thermal p-n junctions: a macroscopic thermal diode based on heterogeneous materials - Yue Zhang; Baotong Li; Pengfei Sun; Yu Hou; Jun Hong; Meng Shi; Liang Zeng; Qingfang Liu (Chemical Engineering Journal, 2025)

Closed-loop recycling of lead iodide precursor from waste organic solvents in the production of perovskite solar cells: Toward sustainable photovoltaics - Qingfang Zou; Zifan Lin; Zhaoyang Li; Guang Hu; Shifa Zhou; Ying Zheng; Liang Huang; Sha Liang; Huabo Duan; Shushan Yuan; Chao Chen; Ling Xu; et al. (Waste Management, 2025)

Organic matter accelerated microbial iron reduction and available phosphorus release in reflooded paddy soils - Xipeng Liu; Yuchen Shu; Kejie Li; Haotian Wang; Qingfang Bi; Haibo Wang; Chengliang Sun; Xianyong Lin (Soil Ecology Letters, 2025)

Gelatin based preservation technologies on the quality of food: a comprehensive review - Qingfang Ying; Shengnan Zhan; Haixia Yu; Jihua Li; Ru Jia; Huamao Wei; Eugeni Roura; Xinle Tan; Zhaohui Qiao; Tao Huang (Critical Reviews in Food Science and Nutrition, 2025)

Adaptive sowing window strategy for improving grain filling and water loss characteristics of film-mulched maize in Northwest China - Xudong Zhang; Haixiang Xiong; Rui Wang; Junjie Li; Zhaoyun Dong; Zhikuan Jia; Qingfang Han (Field Crops Research, 2025)

Polysaccharide modified fish gelatin intelligent hydrogels for reliable monitoring freshness of shrimp (Litopenaeus vannamei) - Qingfang Ying; Shengnan Zhan; Qiuyu Lu; Wenge Yang; Ru Jia; Gaoshang Li; Tao Huang (Food Hydrocolloids, 2025)

Study of condensable particulate matter from stationary combustion sources: Source profiles, emissions, and impact on ambient fine particulate matter - Huanhuan Tong; Yangjun Wang; Ling Huang; Qingfang Su; Xin Yi; Hehe Zhai; Sen Jiang; Hanqing Liu; Jiaqiang Liao; Li Li (Science of The Total Environment, 2024)

Isolation and identification of epiphytic Pichia kudriavzevii from loquat peels and investigation of its fermentation characteristics for liquor production - Qingfang Xu; Wei Huang; Yanqin Li; Jian Cai; Xiu Gao; Xu Bai; Weiliang Liu; Lifang Zhang; Ling Zhu (Archives of Microbiology, 2024)

The long-term nitrogen fertilizer management strategy based on straw return can improve the productivity of wheat-maize rotation system and reduce carbon emissions by increasing soil carbon and nitrogen sequestration - Ziyan Guo; Yang Liu; Xiangping Meng; Xueni Yang; Chi Ma; Huina Chai; Hui Li; Ruixia Ding; Khudayberdi Nazarov; Xudong Zhang; Qingfang Han (Field Crops Research, 2024)

Reducing fertilization with high planting density increases maize yield stability and nitrogen use efficiency in semi-arid areas - Xiaorong Wu; Zhimin Li; Wenjing Li; Xuanke Xue; Linchuan Yang; Jing Xu; Baoping Yang; Ruixia Ding; Zhikuan Jia; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Lutein Loaded in β-Cyclodextrin Metal-Organic Frameworks for Stability and Solubility Enhancements - Hui Zhang; Liyun Dong; Tao Guo; Guoqing Zhang; Xinyue Ye; Xiaojian He; Qingfang Gao; Mubarak G. Bello; Can Peng; Li Wu; Jiwen Zhang (AAPS PharmSciTech, 2024)

Designing regional joint prevention and control schemes of PM2.5 based on source apportionment of chemical transport model: A case study of a heavy pollution episode - Yangjun Wang; Miao Ning; Qingfang Su; Lijuan Wang; Sen Jiang; Yueyi Feng; Weiling Wu; Qian Tang; Shiyu Hou; Jinting Bian; Ling Huang; Guibin Lu; et al. (Journal of Cleaner Production, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Exosomes from porcine serum as endogenous additive maintain function of boar sperm during liquid preservation at 17 °C in vitro - Yang Wang; Qimin Liu; Qingfang Sun; Lijuan Zheng; Tianqi Jin; Heran Cao; Chao Zhu; Long Li; Ye Gong; Fangxia Yang; Wuzi Dong (Theriogenology, 2024)

Hazards of microplastics exposure to liver function in fishes: A systematic review and meta-analysis - Yu Sun; Qingfang Deng; Qiurong Zhang; Xin Zhou; Ruhai Chen; Siyu Li; Qing Wu; Huaguo Chen (Marine Environmental Research, 2024)

Antidote or poison? Digital economy and land-use - Qingfang Liu; Huaxiong Jiang; Jianmei Li; Jinping Song; Xiantian Zhang (Land Use Policy, 2024)

Impact assessment of poverty alleviation on carbon inequality: evidence from households in China - Xiahai Wei; Hujian Li; Yao Wang; Qingfang Wei (Journal of Cleaner Production, 2024)

Spatial correlation and allometric growth relationship between economic development and carbon emission in Lanzhou–Xining urban agglomeration - Qingfang Liu; Jinping Song; Teqi Dai; Huiran Han; Jianhui Xu; Jianmei Li; Enru Wang (Environment, Development and Sustainability, 2024)

Shaping the succession patterns of different soil nutrients, enzyme stoichiometry, and microbial communities through rotation systems - Dan Liu; Yang Liu; Junjie Li; Qin Mo; Junyan Tang; Wenhan Liu; Maksat Batyrbek; Tiening Liu; Xudong Zhang; Qingfang Han (CATENA, 2024)

Higher Available Soil Water Storage at Sowing and Frequency of Rainfall Events During the First Month Enhanced the Inhibitory Effect of Nitrification Inhibitor on Nitrous Oxide Emissions - Xiaorong Wu; Junjie Li; Tao Zhang; Xuanke Xue; Shakeel Ahmad; Baoping Yang; Zhikuan Jia; Xudong Zhang; Qingfang Han (Journal of Soil Science and Plant Nutrition, 2024)

Identification of genomic-wide genetic links between cutaneous melanoma and obesity-related physical traits via cFDR - Shen Lin; Runnan Shen; Jingqian Huang; Yanhan Liu; Hongpeng Li; Qingfang Xu (Genes & Genomics, 2023)

The allometric relationship between carbon emission and economic development in Yangtze River Delta: fusion of multi-source remote sensing nighttime light data - Jianhui Xu; Qingfang Liu; Ning Ruan; Feng Hu; Weizhong Jiang; Yuanyuan Li; Wenhao Ma (Environmental Science and Pollution Research, 2023)

Partitioning evapotranspiration using 18O abundance to understand water use efficiency in maize produced using ridge-furrow mulching system - Jing Xu; Fangjian Li; Xudong Zhang; Zhikuan Jia; Lingling Li; Qingfang Han (Field Crops Research, 2023)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Ensiling pretreatment fortified with laccase and microbial inoculants enhances biomass preservation and bioethanol production of alfalfa stems - Xueyan Bao; Gang Guo; Wenjie Huo; Qinghong Li; Qingfang Xu; Lei Chen (Science of The Total Environment, 2023)

Spatio-temporal accuracy evaluation of MSWEP daily precipitation over the Huaihe River Basin, China: A comparison study with representative satellite- and reanalysis-based products - Lingjie Li; Yintang Wang; Leizhi Wang; Qingfang Hu; Zhenduo Zhu; Liping Li; Chengxi Li (Journal of Geographical Sciences, 2022)

Microbial respiratory thermal adaptation is regulated by r‐/K‐strategy dominance - Hongyang Chen; Qingfang Jing; Xiang Liu; Xuhui Zhou; Changming Fang; Bo Li; Shurong Zhou; Ming Nie (Ecology Letters, 2022)
Microbial thermal adaptation is considered to be one of the core mechanisms affecting soil carbon cycling. However, the role of microbial community composition in controlling thermal adaptation is poorly understood. Using microbial communities from the rhizosphere and bulk soils in an 8‐year warming experiment as a model, we experimentally demonstrate that respiratory thermal adaptation was much stronger in microbial K ‐strategist‐dominated bulk soils than in microbial r ‐strategist‐dominated rhizosphere soils. Soil carbon availability exerted strong selection on the dominant ecological strategy of the microbial community, indirectly influencing respiratory thermal adaptation. Our findings shed light on the linchpin of the dominant ecological strategy exhibited by the microbial community in determining its respiratory thermal adaptation, with implications for understanding soil carbon losses under warming.

Testicular miRNAs and tsRNAs provide insight into gene regulation during overwintering and reproduction of Onychostoma macrolepis - Guofan Peng; Chao Zhu; Qingfang Sun; Jincan Li; Yining Chen; Yingjie Guo; Hong Ji; Fangxia Yang; Wuzi Dong (Fish Physiology and Biochemistry, 2022)

Spatiotemporal variation in near-surface CH4 concentrations in China over the last two decades - Jianhui Xu; Qingfang Liu; Kai Wang; Qiulong Wang; Li Wang; Yuchan Liu; Maoyu Li (Environmental Science and Pollution Research, 2021)

Calculation of instream ecological water requirements under runoff variation conditions: Taking Xitiaoxi River in Taihu Lake Basin as an example - Qin Wang; Shuwen Wang; Qingfang Hu; Yintang Wang; Yong Liu; Lingjie Li (Journal of Geographical Sciences, 2021)

Effects of deficit irrigation combined with rainwater harvesting planting system on the water use efficiency and maize (Zea mays L.) yield in a semiarid area - Peng Zhang; Ting Wei; Yuling Li; Yan Zhang; Tie Cai; Xiaolong Ren; Qingfang Han; Zhikuan Jia (Irrigation Science, 2019)

Establishment and evaluation of a model for predicting 3-month mortality in Chinese patients with hepatic encephalopathy - Yanping Cui; Shan Guan; Jie Ding; Yukai He; Qingfang Li; Sikui Wang; Huiling Sun (Metabolic Brain Disease, 2019)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Tanning performance and environmental effects of nanosized graphene oxide tanning agent - Shenghua Lv; Qingfang Zhou; Ying Li; Yaya He; Haoran Zhao; Shiyu Sun (Clean Technologies and Environmental Policy, 2016)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Multi-scale evaluation of six high-resolution satellite monthly rainfall estimates over a humid region in China with dense rain gauges - Qingfang Hu; Dawen Yang; Zhe Li; Ashok K. Mishra; Yintang Wang; Hanbo Yang (International Journal of Remote Sensing, 2014)

Comparative mapping reveals similar linkage of functional genes to QTL of yield-related traits between Brassica napus and Oryza sativa - FUPENG LI; CHAOZHI MA; QINGFANG CHEN; TOUMING LIU; JINXIONG SHEN; JINXING TU; YONGZHONG XING; TINGDONG FU (Journal of Genetics, 2012)

An extracellular oligopeptide permease may be a potential virulence factor of Vibrio harveyi - Qingfang He; Jixiang Chen; Caifeng Li (Journal of Ocean University of China, 2011)

Molecular Characterization of the Full-Length Coding Sequence of the Caprine Laminin Receptor Gene (RPSA) - Rongyan Zhou; Xianglong Li; Huiqin Zheng; Lanhui Li; Weiyao Quan; Zunan Shen; Jun Tong; Qingfang Yang; Qiang Fu (Biochemical Genetics, 2010)

Alternating Current (AC) Iontophoretic Transport across Human Epidermal Membrane: Effects of AC Frequency and Amplitude - Guang Yan; Qingfang Xu; Yuri G. Anissimov; Jinsong Hao; William I. Higuchi; S. Kevin Li (Pharmaceutical Research, 2008)

Construction of a molecular functional map of rapeseed (Brassica napus L.) using differentially expressed genes between hybrid and its parents - Yuanyuan Li; Chaozhi Ma; Tingdong Fu; Guangsheng Yang; Jingxing Tu; Qingfang Chen; Tonghua Wang; Xingguo Zhang; Chunyan Li (Euphytica, 2006)